Komunikasi Politik Partai Ummat di Media Sosial: Populisme Agama dan Dampaknya pada Demokrasi 2024 - Rizki Insani; Sundawan Salya; Pratama Dahlian Persadha (Jurnal Ilmu Sosial dan Ilmu Politik)
The research aims to analyze the characteristics of using religion-based populist issues as part of the political communication of the Ummat Party, understand its impact on national integration, and examine intelligence efforts to counter the threat of religion-based populism. The research employs a qualitative methodology with a case study approach, involving social media content analysis, interviews, and literature studies to supplement the research data. The findings identify that the Ummat Party consistently produces, reproduces, and distributes hatred, fear, and distortion to criticize various policies implemented by the government under President Joko Widodo's leadership to evoke public emotions. This research is expected to provide a profound understanding of the threat posed by the use of religion-based populist issues and ways to counteract such threats, as well as to offer recommendations as strategic steps in addressing this menace.